UNGKAPAN VERNAKULAR BAHASA INGGRIS-AMERIKA DALAM FILM 12 YEARS A SLAVE (English-American Vernacular Expression in the Movie ’12 Years A Slave’) - Andi Indah Yulianti (Balai Bahasa Sulawesi Selatan, 2014)
Vernacular is uncodified language or unstandardized type of language which is used in daily conversation of informal situation. The purpose of this writing is to explain the forms of vernacular expression in AmericanEnglish in 12 Years A Slave which the script is written by John Ridley and directed by Steve McQueen. The movie is interesting to be observed because the dialogues in this movie consist of non-formal statements and deviated syntax. The vernacular expression discussed in this research is grammatical vernacular and lexical vernacular. The writer uses library research method by reading literatures related to vernacular language. The data obtained in this writing is dialogues in 12 Year A Slave. The writer transcripts spoken conversation from movie into written conversation then describes every situation happened in every dialogue. The vernacular expressions grammatically and lexically in the dialogues are mostly infringe the rules of English grammar. The grammar deviations appear grammatically, such as the deviation of copula be, the vanishing of copula be, the using of multi-negation, the vanishing of subject, the vanishing of auxiliary verb do in interrogative sentence, the deviation of auxiliary verbs do, the vanishing of be and the shortening of going to, and the vanishing of auxiliary verbs have. Meanwhile, the lexically deviations are variant of copula be + not, gunna as variant of going to, cain’t as a variant of the can + not, the linking sound, shortening of the word element, and a variety of lexical variation.